2015
DOI: 10.1109/tia.2015.2443091
|View full text |Cite
|
Sign up to set email alerts
|

Selection Criteria and Robust Optimization of a Traction PM-Assisted Synchronous Reluctance Motor

Abstract: Abstract-In the coming years, the electrification and the deployment of the electric motors in the urban transports will become a reality more and more widespread. The optimization stage of the electric motors usually does not consider in detail the real driving conditions of the car in which the motor is installed. It follows that the actual motor performance in operating points, especially as regards the torque ripple and the efficiency, might be worsen than expected. A robust solution is a required target. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 24 publications
1
27
0
Order By: Relevance
“…A shown before, the maximum output torque of the four machines is different and the Sd-PM machine gives the highest output torque. In general, and in correspondence with the literature [15], adding ferrite PMs in the rotor of a SynRM increases the machine's efficiency. It is worth noting that the efficiency of the Sd-PM machine (Figure 30) is much better than for the other machines over the whole operating range, but especially at low loads.…”
Section: Experimental Validationsupporting
confidence: 77%
See 2 more Smart Citations
“…A shown before, the maximum output torque of the four machines is different and the Sd-PM machine gives the highest output torque. In general, and in correspondence with the literature [15], adding ferrite PMs in the rotor of a SynRM increases the machine's efficiency. It is worth noting that the efficiency of the Sd-PM machine (Figure 30) is much better than for the other machines over the whole operating range, but especially at low loads.…”
Section: Experimental Validationsupporting
confidence: 77%
“…In the literature, much research work on SynRMs and PMaSynRMs can be found [3][4][5][6][7][8][9][10][11][12][13][14][15][16]. For example, in [8], SynRM performance is compared for different electrical steel grades.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, some articles have reported the design of machines under different operating conditions [12][13][14][15]. In [12], the dynamic behaviors of a permanent magnet synchronous machine are investigated in which three different operation conditions such as no load, rated operation, and short circuit are analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…In [13] and [14], by considering the limitation of different load current, the robustness against demagnetization of an ferrite assisted synchronous reluctance machine is studied, and the investigations show that the larger machines have more risk of demagnetization than smaller ones when overload current is applied. In [15], the optimization design of PM synchronous machines is performed to reduce the losses in high speed operation condition, and the methods enlarging operating efficiency especially in high speed light load region are proposed. In summary, the operation characteristics of machines in various operating conditions have been studied extensively.…”
Section: Introductionmentioning
confidence: 99%